2008
DOI: 10.4049/jimmunol.180.7.4540
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Antitumor T Cell Immunity: Comparative Functional Analysis of Interstitial Versus Langerhans Dendritic Cells in a Human Cell Line Model

Abstract: Dendritic cells (DC) are increasingly applied as a cellular adjuvant in immunotherapy of cancer. Two major myeloid DC subsets are recognized: interstitial DC (IDC) that infiltrate connective tissues and Langerhans cells (LC) that line epithelial surfaces. Yet, functional differences between IDC and LC remain to be defined. We recently showed that the CD34+ acute myeloid leukemia cell line MUTZ-3 supports differentiation of both DC-SIGN+ IDC and Langerin-positive Birbeck granule-expressing LC. By comparative fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 48 publications
(44 reference statements)
4
58
1
Order By: Relevance
“…Both subsets were previously reported to be able to migrate to draining LNs and to prime specific Th cells or CTLs (21,22). Besides these two migratory subsets, we also identified two CD1a À LN-resident cDC subsets (CD14 À or CD14 þ ; ref.…”
Section: Introductionmentioning
confidence: 68%
“…Both subsets were previously reported to be able to migrate to draining LNs and to prime specific Th cells or CTLs (21,22). Besides these two migratory subsets, we also identified two CD1a À LN-resident cDC subsets (CD14 À or CD14 þ ; ref.…”
Section: Introductionmentioning
confidence: 68%
“…However, MRP4 protein expression was detected on MUTZ3 progenitor cells and on in vitro cultured immature and mature MUTZ3-DCs and MUTZ3-LCs by immunocytochemistry (data not shown). Because the MUTZ3 cell line functions as a previously described relevant model for in vitro 19,29,30 this cell line was used for further in vitro MRP4 studies. Given the notion that a previous study by Angénieux et al 31 reported MRP4 mRNA expression in MoDC, mRNA levels were also checked by semiquantitative RT-PCR for monocytes and MUTZ3 progenitors as well as for differentiated MoDC and MUTZ3-DCs and MUTZ3-LCs.…”
Section: Mrp4 Knock-down Inhibits Mutz3-lc Migration Toward Ccl19 Andmentioning
confidence: 99%
“…Moreover, cytokine receptors that are associated with DC differentiation such as GM-CSF-R and TNF-α-RI and -RII are up-regulated. In contrast to other AML-derived cell lines, MUTZ-3 cells have a marked DC differentiation capacity since CD1a expression after DC differentiation ranges between 60% and 90% for MUTZ-3 IDC and LC, respectively (66,67). Moreover, MUTZ-3-generated IDC and LC also express intermediate to high levels of co-stimulatory, adhesion, and MHC class I and II molecules, indicating that MUTZ-3 IDC and LC exhibit a true DC phenotype (68).…”
Section: Dcs Produced From Leukemia Cell Linesmentioning
confidence: 99%